Attosecond xuv pulses for complete mapping of the time-dependent wave packets of D2+ - Tong, X. M.; Lin, C. D. (My University, 2006)
We have shown that the whole time-dependent vibrational wave packet of D2+ ions can be reconstructed from the kinetic energy release of the D+ ion pairs when it is probed with an attosecond xuv pulse. Such a full interrogation of the wave packet will pave the way for controlling the generation of tailor-designed wave packets for favorable chemical reaction paths, as well as for probing the time evolution of their interaction with the medium.